Filling vacancies in a Prussian blue analogue using mechanochemical post-synthetic modification - Cattermull, J; Wheeler, S; Hurlbutt, K; Pasta, M; Goodwin, AL (Royal Society of Chemistry, 2020)
Mechanochemical grinding of polycrystalline powders of the Prussian blue analogue (PBA) Mn[Co(CN)6]2/3□1/3·xH2O and K3Co(CN)6 consumes the latter and chemically modifies the former. A combination of inductively-coupled plasma and X-ray powder diffraction measurements suggests the hexacyanometallate vacancy fraction in this modified PBA is reduced by approximately one third under the specific conditions we explore. We infer the mechanochemically-driven incorporation of [Co(CN)6]3− ions onto the initially-vacant sites, coupled with intercalation of charge-balancing K+ ions within the PBA framework cavities. Our results offer a new methodology for the synthesis of low-vacancy PBAs.